SOSIALISASI PAJAK BUMI DAN BANGUNAN KEPADA KARANG TARUNA DI DESA KARANGLO, SEDAYU, BANTUL - Manurung, Siska; Rochmad Bayu Utomo (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2025)
The Land and Building Tax (PBB) socialization activity was carried out to increase the understanding of Karang Taruna members in Karanglo Village, Sedayu, Bantul about the importance of this tax for regional development. With methods that include observation, material preparation, interactive socialization, and evaluation, this activity lasts for one month. The observation results showed that the participants' initial understanding of the PBB was still low. After the implementation of socialization, there was a significant increase in participants' understanding, with the average evaluation score increasing from 45% to 85%. The systematic preparation of materials and a participatory approach to socialization contributed to this success. This activity not only raises awareness about tax obligations but also encourages the active participation of the younger generation in village development. Thus, this program has succeeded in achieving its goal of being an effective tax education effort. The results and discussions regarding the socialization of Land and Building Tax to members of the Youth Organization in Karanglo Village showed a significant increase in participants' understanding of Land and Building Tax.